2009
DOI: 10.1080/13606710902752653
|View full text |Cite
|
Sign up to set email alerts
|

Urban park visiting habits and leisure activities of residents in Hong Kong, China

Abstract: This paper examines urban park visiting behaviour of Hong Kong residents. It uses the findings from a telephone survey conducted in 2005, in which 758 Hong Kong residents were successfully interviewed. The survey found that there were slightly more infrequent park users than frequent park users (FPUs) in Hong Kong. About 8% of the respondents said that they never visit urban parks. Of the 43% of FPUs, many of them were either elderly or adolescents. The survey revealed that many users visited parks near their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 11 publications
5
36
2
Order By: Relevance
“…Also, the elderly, new immigrants and economically deprived individuals living in public housing estates were often indifferent to opinion surveys. An unusually low response rate (17.5%) was recorded in a recent local telephone survey concerning urban parks (Wong, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Also, the elderly, new immigrants and economically deprived individuals living in public housing estates were often indifferent to opinion surveys. An unusually low response rate (17.5%) was recorded in a recent local telephone survey concerning urban parks (Wong, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Lo, Yiu, & Lo, 2003;Wang et al, 2015;Wong, 2009) (See Appendix A). The questionnaire contained items for the nine variables shown in Fig.…”
Section: Questionnaire Design and Data Collectionmentioning
confidence: 95%
“…Lo et al, 2003;Wong, 2009; Van Herzele & Wiedemann, 2003 FAC2 Urban green spaces provide sufficient ancillary facilities. (e.g., drinking, washroom) FAC3 Urban green spaces provide sufficient catering services.…”
Section: Constructsmentioning
confidence: 98%
See 1 more Smart Citation
“…A survey conducted with 758 residents in Hong Kong by telephone interviews showed that parks are mostly used by older people, and the park users generally prefer walking and physical exercises. It was determined that they believe these activities contribute to their physical and psychological health (Wong, 2009). …”
Section: Public Health Protectionmentioning
confidence: 99%